Comparative Analysis of Manual, Rotary and Reciprocal Systems on Primary Teeth Root Canals: An In Vitro Scanning Electron Microscopy Study - Murat Şirin; Tamer Tüzüner; Ozgul Baygın; Sema Aydınoğlu; İpek Arslan (Cumhuriyet University, 2019)
Objective: To evaluate the residual debris and smear layer formation, and also preparation time of one or multifile manual, rotary, and reciprocal systems on primary teeth. Materials and methods: A total of 75 primary mandibular molar teeth were randomly divided to five groups (n=15). The distal canals of teeth were shaped with each of the K file, Protaper, Twisted File, OneShape, and Reciproc systems. Preparation time was also recorded. Longitudinal sections groups were prepared and processed for observation under scanning electron microscopy (SEM) at a standard magnification of X1000 for smear layer and X200 for residual debris. The presence of smear layer and residual debris was evaluated by two trained operators. The data of preparation time and also debris and smear scores were analyzed using ANOVA and the Kruskal-Wallis test, respectively.   Results: Reciproc and OneShape systems had significantly less instrumentation time than all other groups (p<0.001). The results of statistical analyses were the same for the residual debris and smear layer scores. In the coronal thirds of the canals, the canal preparation with the Protaper system resulted in significantly less debris and smear layer compared with the OneShape system (p=0.015). In the middle thirds of the canals, OneShape and Reciproc systems had more residual debris and smear layer than the Protaper system (p<0.05). In the apical thirds of the canals, the use of the Protaper instruments resulted in less debris and smear layer than the Reciproc system (p=0.034). Conclusion: Within the limits of this study, the Protaper system, which showed better cleaning efficacy and was also faster than the manual system, can be an effective alternative to other systems in the root canal treatment of primary molars. More in vitro and clinical investigations are needed on root canal treatment of primary teeth.